Molecular Epidemiology of Extraintestinal Pathogenic Escherichia coli Causing Hemorrhagic Pneumonia in Mink in Northern China - Yu, Ying; Hu, Bo; Fan, Huanhuan; Zhang, Hailing; Lian, Shizhen; Li, Hongye; Li, Shuangshuang; Yan, Xijun; Wang, Shaohui; Bai, Xue (Frontiers in Cellular and Infection Microbiology, 2021)
The molecular epidemiology and biological characteristics of Escherichia coli associated with hemorrhagic pneumonia (HP) mink from five Chinese Provinces were determined. From 2017 to 2019, 85 E. coli strains were identified from 115 lung samples of mink suffering from HP, These samples were subjected to serotyping, antimicrobial susceptibility, detection of virulence genes, phylogenetic grouping, whole-genome sequencing, drug resistant gene, multilocus sequence typing (MLST) and biofilm-forming assays. E. coli strains were divided into 18 serotypes. Thirty-nine E. coli strains belonged to the O11 serotype. Eighty-five E. coli strains were classified into seven phylogenetic groups: E (45.9%, 39/85), A (27.1%, 23/85), B1 (14.1%, 12/85), B2 (3.7%, 3/85), D (3.7%, 3/85), F (2.4%, 2/85) and clade Ⅰ (1.2%, 1/85). MLST showed that the main sequence types (STs) were ST457 (27/66), All E. coli strains had ≥4 virulence genes. The prevalence of virulence was 98.8% for yijp and fimC, 96.5% for iucD, 95.3% for ompA, 91.8% for CNF-Ⅰ, 89.4% for mat, 82.3% for hylf, and 81.2% for ibeB. The prevalence of virulence for iss, cva/cvi, aatA, ibeA, vat, eae, and Sta was 3.5–57.6%. All E. coli strains were sensitive to sulfamethoxazole, but high resistance was shown to tetracycline (76.5%), chloramphenicol (71.8%), ciprofloxacin (63.5%) and florfenicol (52.9%), resistance to other antibiotics was 35.3–16.5%. The types and ratios of drug-resistance genes were Tet(A), strA, strB, sul2, oqxA, blaTEM-1B, floR, and catA1 had the highest frequency from 34%-65%, which were consistent with our drug resistance phenotype tetracycline, florfenicol, quinolones, chloramphenicol, the bla-NDM-I and mcr-I were presented in ST457 strains. Out of 85 E. coli strains, Six (7.1%) possessed a strong ability, 12 (14.1%) possessed a moderate ability, and 64 (75.3%) showed a weak ability to form biofilm. Our data will aid understanding of the epidemiological background and provide a clinical basis for HP treatment in mink caused by E. coli.